Context-agile encryption for high speed communication networks. - Pierson, Lyndon G. (Computer communication review.)
Different applications have different security requirements for data privacy, data integrity, and authentication. Encryption is one technique that addresses these requirements. Encryption hardware, designed for use in high-speed communications networks, can satisfy a wide variety of security requirements if the hardware implementation is key-agile, key length-agile, mode-agile, and algorithm-agile. Hence, context-agile encryption provides enhanced solutions to the secrecy, interoperability, and quality of service issues in high-speed networks. Moreover, having a single context-agile encryptor at an ATM aggregation point (such as a firewall) reduces hardware and administrative costs. While single-algorithm, key-agile encryptors exist, encryptors that are agile in a cryptographic robustness sense, are still research topics.